Factors That Affect Earnings Response Coefficient in Industrial Companies Listed in Amman Stock Exchange (ASE) - Al-Quraan, Salam; Al-Debi’e, Mamoun (Jordan Journal of Business Administration, 2020)
This study aimed at determining the effect of selected company characteristics; specifically, firm size, profitability, growth opportunities and leverage on the slope coefficient (earnings response coefficient) of the returns-earnings relationship. The study used a sample of 66 industrial companies listed in Amman stock exchange over the period (2006-2016) with (620) company-year observations. Size was measured using total assets at the beginning of the period, profitability was measured using the return on assets and the return on equity, growth opportunities was measured using market value to book value ratio and Tobin’s Q and finally, leverage was measured using total debt to total asstes ratio and total debt to equity ratio.In order to identify the effect of company characteristics on the earnings response coefficient, the sample observations were classified into two sub-samples according to each of company characteristics; then, the simple regression model of the returns-earnings model was run for each sub-sample. The dependent variable in the model was annual stock market return and the independent variable was the level of earnings measured by dividing earnings per share by the stock market price at the beginning of the study window.The study found that the earnings response coefficient is negatively affected by the size of the company, its leverage and growth opportunities and positively by profitability. Accordingly, we recommend that stock market participants depend on the return on equity in making their investment decisions, since it recorded the highest earnings response coefficient. Furthermore, we recommend that stock market participants rely on the debt to total assets ratio rather than the debt to equity ratio in taking their financing decisions, since it recorded a higher explanatory power in explaining the variation in the earnings response coefficient.